Dynamical analysis of a satellite‐observed anticyclonic eddy in the northern Bering Sea. Issue 5 (27th May 2016) - Li, Yineng; Li, Xiaofeng; Wang, Jia; Peng, Shiqiu
Abstract: The characteristics and evolution of a satellite‐observed anticyclonic eddy in the northern Bering Sea during March and April 1999 are investigated using a three‐dimensional Princeton Ocean Model (POM). The anticyclonic‐like current pattern and asymmetric feature of the eddy were clearly seen in the synthetic aperture radar (SAR), sea surface temperature, and ocean color images in April 1999. The results from model simulation reveal the three‐dimensional structure of the anticyclonic eddy, its movement, and dissipation. Energy analysis indicates that the barotropic instability (BTI) is the main energy source for the growth of the anticyclonic eddy. The momentum analysis further reveals that the larger magnitude of the barotropic pressure gradient in the meridional direction causes the asymmetry of the anticyclonic eddy in the zonal and meridional directions, while the different magnitudes of the meridional baroclinic pressure gradient are responsible for the different intensity of currents between the northern and southern parts of the anticyclonic eddy. Key Points: An anticyclonic eddy was detected by SAR, SST, and ocean color images in 21 April 1999 The barotropic instability is the main energy source for the growth of the eddy The dynamical reasons for the asymmetric structure of the eddy are investigated